2015
DOI: 10.1039/c4cy00888j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic behaviour of a novel Fe(iii) Schiff base complex in the mild oxidation of cyclohexane

Abstract: An iron coordination compound, possessing an unsaturated coordination environment, has been prepared by reaction of FeCl3 with a polydentate Schiff base revealing a complex catalytic behaviour in the mild oxidation of cyclohexane by hydrogen peroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 91 publications
1
12
0
Order By: Relevance
“…[138] Thec omplexw as assembled insitu,a nd was found to adopt as lightly distorted octahedrals tructure,w ith the distaln itrogen of the piperazine ringp rotonated.V ery lowc atalyst loadings (0.05-0.2 mol%) are requiredt od isplay an impressive catalytic activity in cyclohexane oxidation by H 2 O 2 , with 37% yield and 900 TON (entry 10 of Table 3). HNO 3 (in am inimum acid:catalyst ratio of 50:1)i s necessary to achieve these results.A ccordingt othe authors,t he role of nitric acid is to induce ac atalyst reorganization in combination with H 2 O 2 .B y-products generated by ar adical chain oxidation were detected in at otal yield of 1-5% depending on catalyst concentration.…”
Section: Other Imine-based Iron Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…[138] Thec omplexw as assembled insitu,a nd was found to adopt as lightly distorted octahedrals tructure,w ith the distaln itrogen of the piperazine ringp rotonated.V ery lowc atalyst loadings (0.05-0.2 mol%) are requiredt od isplay an impressive catalytic activity in cyclohexane oxidation by H 2 O 2 , with 37% yield and 900 TON (entry 10 of Table 3). HNO 3 (in am inimum acid:catalyst ratio of 50:1)i s necessary to achieve these results.A ccordingt othe authors,t he role of nitric acid is to induce ac atalyst reorganization in combination with H 2 O 2 .B y-products generated by ar adical chain oxidation were detected in at otal yield of 1-5% depending on catalyst concentration.…”
Section: Other Imine-based Iron Complexesmentioning
confidence: 99%
“…Thec omplexw as directly assembled in the reactionv essel (see Scheme 18). [138] Aromatic sulfides were converted to the corresponding sulfoxidesw ith moderate yields (21-44%) and good enantioselectivities (25-90% ee). Addition of benzoic acid (1 mol%) exertedahighly beneficial effect on bothy ieldsa nd enantioselectivity of the transformation (36-78% yields and4 4-96% ee).…”
Section: Other Imine-based Iron Complexesmentioning
confidence: 99%
“…In contrast to that alkane oxidation reactions catalysed by a Schiff base iron(III) complex bearing salicylidene derived ligand 44 are dominated by a hydroxyl radical-based mechanism. 119 Caradonna et al 120,121 reported the application of a diiron(II) complex bearing tetracoordinate phenolate ligand 45 (Figure 9) in cyclohexane oxidation catalysis using 2-methyl-1phenylprop-2-yl hydroperoxide (MPPH) as oxygen atom donor. The complex shows high catalytic efficiency (230 turnovers) and selectivity for alcohol formation.…”
Section: Iron Nonheme Complexes Bearing C- O-and S-donor Ligandsmentioning
confidence: 99%
“…During the past several decades, many metals have been studied in catalytic activation and functionalization of carbon-hydrogen bonds. The reader is directed to selected recent examples with gold [123], cobalt [124][125][126] chromium [127], copper [128][129][130][131] iron [132][133][134][135], iridium [136], manganese [137][138][139], molybdenum [140], nickel [141], osmium [142][143][144][145][146][147][148], palladium [149][150][151], rhenium [152], rhodium [153,154], ruthenium [155,156], and vanadium [157,158].…”
Section: Metal Ions Most Active In Oxidation Catalysismentioning
confidence: 99%